DETERMINING RIVER WATER QUALITY STATUS BASED ON THE POLLUTION INDEX METHOD AS CONTROL OF ENVIRONMENTAL QUALITY - Ridwan Adi Surya; Devianto Girsang; Sahindomi Bana; Kahirun; La Ode Siwi; La Ode Midi (Jurnal Infrastruktur, 2021)
The rapid pace of development in Kendari has had an inevitable negative impact on environmental quality, including water quality degradation in Wanggu River. River water quality degradation is influenced by anthropogenic activities such as felling trees for land clearing, agricultural waste, and disposal of organic and inorganic waste into river bodies. These activities certainly affect the decline in the water quality of the Wanggu River. This study aims to determine the water quality status of Wanggu River based on the pollution index method. This study was conducted in September - October 2019. To find out the water sampling points, the stations were determined, namely station I, station II, and station III using the observation method. Water samples at the three stations were tested for water quality at Laboratory of Biology, Faculty of Mathematics and Natural Sciences, Halu Oleo University, to analyze physical parameters (temperature, TDS, and TSS), chemical parameters (pH, DO, BOD, COD, Nitrate, Nitrite, Oil and Fat, Detergent), and Microbiological Parameters (Total Coliform). Determination of the water quality of the Wanggu River was carried out using the Pollution Index Method. Based on the results of the Analysis of Pollution Index Method, the water samples from Wanggu River at stations I, II, and III obtained pollution index values of 1.62, 1.79, and 1.73 respectively. Therefore, the pollution index of the Wanggu River at the three stations was at a lightly polluted quality status. Besides, some parameters that did not meet quality standards included chemical parameters, namely Biological Oxygen Demand (BOD) and Dissolved Oxygen (DO), so that the water quality status of Wanggu River was classified as lightly polluted based on class 3 (three) water quality standards set by Government Regulation No. 82 of 2001.